Strangler unmasked: Parasitism of Cystoderma amianthinum by Squamanita paradoxa and S. pearsonii. (June 2019) - Griffith, Gareth W.; Gajda, Krzysztof Piotr; Detheridge, Andrew P.; Douglas, Brian; Bingham, John; Turner, Alex; Bowmaker, Victoria; Evans, Debbie A.; McAdoo, William G.; Dentinger, Bryn T.M.
Abstract: The mushroom-forming genus Squamanita comprises 10 described species, all parasitic on basidiomes of other members of the order Agaricales, including members of the genera Cystoderma, Galerina, Inocybe and Hebeloma . Here we report an anatomical investigation of the stipitate "mycocecidium' (=fungus gall) formed on the basidiome of Cystoderma amianthinum ("powdercap") by S. paradoxa ("powdercap strangler"), alongside the development of taxon-specific-PCR primer to localise the presence of S. paradoxa / C. amianthinum mycelia within mycocecidia, in associated plant tissues and apparently healthy host basidiomes. Dissection of fungarium samples also confirmed these findings, whilst ITS barcode sequencing of all available samples held at the RBG Kew and Edinburgh fungaria did not reveal any variation in ITS sequences within UK populations of S. paradoxa or the closely related S. pearsonii . The absence of any 13 C or 15 N isotopic differences between C. amianthinum and S. paradoxa suggests that S. paradoxa is nutritionally dependent on its host. The status of C. amianthinum as host of S. pearsonii is also confirmed.